Accounting as a Structuring Governance Mechanism: - Patrice Gelinas; Lisa Baillargeon (Journal of Accounting, Business and Management (JABM), 2023)
This paper seeks to contribute to the debate on how to conceptualise structure and agency in accounting through a longitudinal exploration of the financial statements of the St. Anselm Foundry over almost a century. We argue that linkages between the firm’s information production choices, its governance structure and the socio-economic context in which it operates are better explained as a function of different interacting structural conditions, as mediated through human agency, than with agency theory alone. This argument is consistent with a proposal by Kilfoyle and Richardson (2011), but our analysis expands the demonstration of such dualism from management accounting to financial accounting.